Microalgae-mediated tandem culture of shrimp and bivalve: an environmental and health co-benefits solution for phosphorus recovery and emission reduction - Ma, Shuonan; Dong, Xumeng; Luo, Cheng; Zhao, Chunpu; Xu, Jilin (Frontiers in Marine Science, 2023)
Phosphorus (P) accumulation in aquaculture systems harms our environment beyond acceptable limits. Devising strategies that potentially recover P from aquaculture systems in a reusable bioresource form is paramount, and aligns with the circular economy policy. In this study, we constructed two culture models, monoculture (Mon) and tandem culture (Tan), using Exopalaemon carinicauda and Mercenaria mercenaria. By monitoring the performance of rearing organisms, P dynamic patterns, and pollutant emissions, we found that: ⅰ) Compared with the Mon system, the Tan system demonstrated no differences in the performance of E. carinicauda and M. mercenaria, suggesting that the Tan model was viable in terms of fisheries yields; ⅱ) P in the Tan system could be efficiently recovered and removed from water and sediment, as indicated by the lower phosphate concentration in water (0.01 mg L−1), and the decrease of labile P in surficial sediment (from 0.04 to 0.02 mg L−1). A combination of assimilatory and dissimilatory processes, mediated by phototrophic (bait-microalgae) and heterotrophic organisms (bivalves), appeared to be the primary mechanism for P utilization and removal; ⅲ) The Tan system reduced pollutant emissions four folds lower than the Mon system due to its minimal tailwater discharge (10%, 230 L). The emissions of total P, phosphate, total organic carbon, ammonium, and chemical oxygen demand from Tan systems were respectively 19 mg m−2 d−1, 2 mg m−2 d−1, 2 g m−2 d−1, 38 mg m−2 d−1, and 11 g m−2 d−1, 1.3, 1.7, 1.4, 1.3, and 1.2 times lower than those observed in the Mon systems. The eco-friendly Tan culture model fully exploited the pond culture resources, an environmental and health co-benefits solution for P recovery and emission reduction.